2021
DOI: 10.1038/s42003-021-01856-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile accelerated specific therapeutic (FAST) platform develops antisense therapies to counter multidrug-resistant bacteria

Abstract: Multidrug-resistant (MDR) bacteria pose a grave concern to global health, which is perpetuated by a lack of new treatments and countermeasure platforms to combat outbreaks or antibiotic resistance. To address this, we have developed a Facile Accelerated Specific Therapeutic (FAST) platform that can develop effective peptide nucleic acid (PNA) therapies against MDR bacteria within a week. Our FAST platform uses a bioinformatics toolbox to design sequence-specific PNAs targeting non-traditional pathways/genes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…This methodology is not only rapid, but it results in highly specific antisense sequences. The authors utilized the platform to design antisense compounds that act as antibiotics against five multidrug resistant Enterobacteriaceae clinical isolates and an antisense compound that modifies the action of carbapenem against a carbapenem-resistant E. coli strain [95,96]. In the latter case, the target genes were selected following a novel approach.…”
Section: Steric Hindrancementioning
confidence: 99%
“…This methodology is not only rapid, but it results in highly specific antisense sequences. The authors utilized the platform to design antisense compounds that act as antibiotics against five multidrug resistant Enterobacteriaceae clinical isolates and an antisense compound that modifies the action of carbapenem against a carbapenem-resistant E. coli strain [95,96]. In the latter case, the target genes were selected following a novel approach.…”
Section: Steric Hindrancementioning
confidence: 99%
“…Bioinformatics is also bringing a boost for antisense therapies, with the facile accelerated specific therapeutic (FAST) platform being the most recent platform to develop antisense therapies to combat MDR bacteria [ 164 ]. Aunins et al used FAST to create PNAs against CRE bacterial genes identified by transcriptomics.…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
“…The link between miR-2392 and COVID-19 infection prompted the develop of an effective antiviral approach for COVID-19 by inhibiting miR-2392. We used the Nanoligomer platform to develop an effective antisense-based therapeutic against human miR-2392 (Eller et al, 2021), termed SBCov207 (Fig. 6A).…”
Section: Inhibiting Mir-2392: a Novel Antiviral Covid-19 Therapeuticmentioning
confidence: 99%